2013
DOI: 10.4269/ajtmh.2012.12-0223
|View full text |Cite
|
Sign up to set email alerts
|

Host Selection of Potential West Nile Virus Vectors in Puerto Barrios, Guatemala, 2007

Abstract: Abstract. The selection of vertebrate hosts by Culex mosquitoes relative to West Nile virus (WNV) transmission in neotropical countries such as Guatemala is not described. This study determined the feeding patterns of Cx. quinquefasciatus and Cx. nigripalpus and estimated the relative contribution of two common and frequently infected wild bird species, Turdus grayi and Quiscalus mexicanus, to WNV transmission. Engorged mosquitoes were collected from rural and urban habitats after the dry and wet seasons in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…quinquefasciatus and Cx. tarsalis have observed that blood meals from grackles and other icterids are detected with lower frequency than expected from the relative abundance of these birds within the broader avian community, suggesting reduced host selection of icterids by these mosquitoes (Kent et al 2009; Thiemann et al 2012; Kading et al 2013). However, whether this is due to reduced host preference or to low survival of mosquitoes that select icterids for blood meals is difficult to determine.…”
Section: Discussionmentioning
confidence: 97%
“…quinquefasciatus and Cx. tarsalis have observed that blood meals from grackles and other icterids are detected with lower frequency than expected from the relative abundance of these birds within the broader avian community, suggesting reduced host selection of icterids by these mosquitoes (Kent et al 2009; Thiemann et al 2012; Kading et al 2013). However, whether this is due to reduced host preference or to low survival of mosquitoes that select icterids for blood meals is difficult to determine.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, in the United States, Guatemala and Mexico, a much higher prevalence of avian blood was found in Cx. quinquefasciatus mosquitoes (59.9%, 85% and 82%, respectively) captured outside houses . A large number of factors influence the feeding behaviour of Cx.…”
Section: Introductionmentioning
confidence: 99%
“…humeralis in this region [ 25 ]. Nonhuman vertebrates such as chickens [ 29 , 30 ] also contribute to the persistence of these viruses, as they usually serve as reservoirs for various arboviruses. In this work, an increase in the population of Mansonia spp.…”
Section: Discussionmentioning
confidence: 99%